2009
DOI: 10.3324/haematol.2009.011205
|View full text |Cite
|
Sign up to set email alerts
|

TET2 gene mutation is a frequent and adverse event in chronic myelomonocytic leukemia

Abstract: BackgroundAcquired somatic deletions and loss-of-function mutations in one or several codons of the TET2 (Ten-Eleven Translocation-2) gene were recently identified in hematopoietic cells from patients with myeloid malignancies, including myeloproliferative disorders and myelodysplastic syndromes. The present study was designed to determine the prevalence of TET2 gene alterations in chronic myelomonocytic leukemias. Design and MethodsBlood and bone marrow cells were collected from 88 patients with chronic phase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
181
3
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 229 publications
(192 citation statements)
references
References 23 publications
(74 reference statements)
7
181
3
1
Order By: Relevance
“…These can broadly be divided into four categories: mutations involving epigenetic regulator genes such as EZH2, ASXL1, TET2, DNMT3A, IDH1, and IDH2 [9,10,14,27], mutations involving the spliceosome machinery such as SF3B1, SRSF2, U2AF35, ZRSR2, SF3A1, PRPF40B, U2AF65, and SF1 [13,14,19,20], mutations involving DNA damage response genes such as Tp53 [28], and mutations involving genes regulating cellular/receptor tyrosine kinases and (13) 12 (100) 9 (75) 3 (25) delP95R-R102-7 (8) 7 (100) 3 (43) 1 (14) R94-P95insR-1 (1) 1 ( (25) 5 (100) 5 (100) 0 (0) Q157G-1 (5) 0 (0) 0 (0) 1 (100) R158H-1 (5) 1 (100) 1 (100) 0 (0) CMML-1, chronic myelomonocytic leukemia-1; SF3B1, splicing factor 3B, subunit 1; SRSF2, serine/arginine-rich splicing factor 2; U2AF35, U2 small nuclear RNA auxiliary factor 1.…”
Section: Discussionmentioning
confidence: 99%
“…These can broadly be divided into four categories: mutations involving epigenetic regulator genes such as EZH2, ASXL1, TET2, DNMT3A, IDH1, and IDH2 [9,10,14,27], mutations involving the spliceosome machinery such as SF3B1, SRSF2, U2AF35, ZRSR2, SF3A1, PRPF40B, U2AF65, and SF1 [13,14,19,20], mutations involving DNA damage response genes such as Tp53 [28], and mutations involving genes regulating cellular/receptor tyrosine kinases and (13) 12 (100) 9 (75) 3 (25) delP95R-R102-7 (8) 7 (100) 3 (43) 1 (14) R94-P95insR-1 (1) 1 ( (25) 5 (100) 5 (100) 0 (0) Q157G-1 (5) 0 (0) 0 (0) 1 (100) R158H-1 (5) 1 (100) 1 (100) 0 (0) CMML-1, chronic myelomonocytic leukemia-1; SF3B1, splicing factor 3B, subunit 1; SRSF2, serine/arginine-rich splicing factor 2; U2AF35, U2 small nuclear RNA auxiliary factor 1.…”
Section: Discussionmentioning
confidence: 99%
“…[10][11][12][13]49 However, a worse prognosis and acute transformation has been linked to ASXL1 mutations. 23 In contrast, the reports on the prognostic effect of TET2 mutations were controversial, 10,12,13 but our study suggests that they do not convey additional negative effects on prognosis, at least in this very homogenous and well-defined CMML cohort.…”
Section: Discussionmentioning
confidence: 99%
“…8,9 Recently, several genes have been found mutated in myeloid malignancies, including CMML. [10][11][12][13] These discoveries were facilitated by single nucleotide polymorphism array (SNP-A) karyotyping, which enables detection of somatic regions of copy number neutral loss of heterozygosity (CN-LOH), also called uniparental disomy (UPD). In CMML homozygous mutations in CBL and TET2 are associated with regions of UPD.…”
Section: Introductionmentioning
confidence: 99%
“…11,12 Other studies found TET2 mutations in 3 of 15 (20%), 14 6 of 17 (35%), 15 and 29 of 69 (42%) 16 of CMML patients, as well as 13 of 38 (34%) cases of aCML. 17 The largest series so far is reported in this issue of Haematologica by Kosmider et al 18 who…”
mentioning
confidence: 99%